Detection of cancerous masses for screening mammography using discrete wavelet transform-based multiresolution markov random field...Proceedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston, TX, May 6-9, 1999 - Zheng L; Chan AK; McCord G; Wu S; Liu JS (Journal of Digital Imaging)
When cancerous masses are embedded in and camouflaged by varying densities of parenchymal tissue structures, they are difficult to visually detect on mammograms. We present a novel algorithm based on the discrete wavelet transform (DWT) and multiresolution markov random field (MMRF) that will single out the suspicious masses to assist the attending radiologist in making decisions. Copyright (c) 1999 by W.B. Saunders Company